2000
DOI: 10.1097/00004770-200012000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of Root Canal Filling Materials to Three Different Human Cell Lines

Abstract: The aim of this study was to investigate the biological compatibility of five root canal sealers (Sealapex, Endion, Super-EBA, Ketac-Endo, and AH Plus) and regular and calcium hydroxide-based gutta-percha in three different human cell lines. Cultures without root canal sealers were used as controls. Cell growth, cell morphology, cell viability, protein content of the cells, and prostaglandin E2 (PGE2) release were used as parameters to determine the cytotoxicity of the materials. The protein content of the thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
2
5

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 18 publications
4
49
2
5
Order By: Relevance
“…10,17 However, Chang et al, 29 showed only a moderate cytotoxicity to periodontal ligament fibroblasts at 3 and 18 h. Regardless of time, this cytotoxicity probably resulted from components/additives such as polymethylene methyl salicylate resin and isobutyl salicylate (Table 1) present in Sealapex. 30 Roth Root 801 proved to be a cytotoxic material at day 1, in agreement with the results of Key et al 17 In contrast, Willershausen et al, 16 using the prostaglandin release assay in gingival fibroblast cultures, found a relatively low cytotoxic effect of Super-EBA, another reinforced zinc oxide-eugenol material, at longer times, while the eugenol-based Roth Root 801 still demonstrated a high cytotoxic effect by day 7 (Figure 1). This phenomenon possibly correlates with the results of Schwarze et al, 21 who described, in a study with 3T3 and HPL cells, that endomethasone strongly inhibited mitochondrial activity during the first 5 h, very likely due to the release of the cytotoxic substance eugenol.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…10,17 However, Chang et al, 29 showed only a moderate cytotoxicity to periodontal ligament fibroblasts at 3 and 18 h. Regardless of time, this cytotoxicity probably resulted from components/additives such as polymethylene methyl salicylate resin and isobutyl salicylate (Table 1) present in Sealapex. 30 Roth Root 801 proved to be a cytotoxic material at day 1, in agreement with the results of Key et al 17 In contrast, Willershausen et al, 16 using the prostaglandin release assay in gingival fibroblast cultures, found a relatively low cytotoxic effect of Super-EBA, another reinforced zinc oxide-eugenol material, at longer times, while the eugenol-based Roth Root 801 still demonstrated a high cytotoxic effect by day 7 (Figure 1). This phenomenon possibly correlates with the results of Schwarze et al, 21 who described, in a study with 3T3 and HPL cells, that endomethasone strongly inhibited mitochondrial activity during the first 5 h, very likely due to the release of the cytotoxic substance eugenol.…”
Section: Discussionsupporting
confidence: 84%
“…AL-Nazhan 16 have demonstrated that diploid human fibroblasts of gingival and nasal origin present improved sensitivity when compared with transformed epithelial tumor cells. This may be a problem commonly faced in studies with transformed cells, which are usually aneuploid.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Disks were seeded at a density of 4 × 10 3 cells/cm², and allowed to adhere for 30 minutes at 37°C. Cells were then incubated in α-MEM supplemented with 10% fetal bovine serum (FBS; Invitrogen, Carlsbad, USA) for 48 hours at 37°C.…”
Section: Cell Vitality Testsmentioning
confidence: 99%
“…Culture and quantitative measurement of human diploid fibroblasts are an appropriate model for identifying the early cytotoxic effects of dental materials. 11 In this in vitro study, we evaluated the effect of a cordless gingival retraction paste on sterile titanium disks. The surface chemistry was first determined using energy-dispersive X-ray spectroscopy (EDS), and further investigated using laser ablation inductively coupled plasma mass spectrometry (LA-ICP-MS).…”
Section: Introductionmentioning
confidence: 99%